News Sentiment, News Intensity, and Price Movement of Indonesia’s 45 Most Liquid Stock Index - M Nagib; Z A Husodo (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study analyzed the sentiment of the constituent news of the LQ45 index on its index movement by considering the news intensity. Two Sentiment analysis methods are used in this study. The Loughran and McDonald’s dictionary as a measure of financial sentiment, then TextBlob sentiment analysis as a measure of general sentiment. We found that news intensity decreased during the financial crisis. Interestingly, news intensity increased significantly after the Covid-19 crisis. Then the constituent news sentiment has a relatively strong correlation with the index movement. Through linear regression analysis, the evidence suggests that the effect of sentiment on index returns is more significant when news intensity increases. Derived from these findings, we concluded that news sentiment is one of the unignorably price-forming factors in further analysis.